Mechanical alloying characteristic and thermal stability of Al78Fe20Zr2 amorphous powders - Zhou, Shuzhu; Wang, Wenwu (Rare metals, 2010)
The powders of pure Al, Fe, and Zr for preparing Al78Fe20Zr2 were subject to a high-energy planetary ball milling.The microstructure evolution of the mixtures at the different intervals of milling was characterized by X-ray diffraction（XRD）, transmission electron microscopy（TEM） and differential scanning calorimetry（DSC）.It was found that a nearly complete amorphization could be achieved in the mixtures after ball milling for 23 h.Further ball milling led to the crystallization of the amorphous powders.A long time ball milling, e.g., 160 h, led to a complete crystallization of the amorphous powders and the formation of Al3Zr and Al13Fe4.The crystallization products caused by ball milling are almost the same as that produced by isothermal annealing of the amorphous powders in vacuum at 800 K for 1 h.